In vivo and in vitro susceptibility and inflammatory response of postnatal mouse cortical neurons and glial cells to zika virus infection - María-Angélica Calderón-Peláez; Myriam L. Velandia-Romero; Jaime E. Castellanos (PLoS ONE, 2025)
Zika virus (ZIKV) poses a significant threat to neural tissue, causing substantial damage to unborn children exposed to the virus in utero , with consequences that can manifest even after birth, despite being born with a normal head circumference. Regardless of the extensive research, the interactions between ZIKV and the nervous system cells remain insufficiently understood, particularly regarding how neuronal responses influence broader inflammatory and viral dynamics especially in postnatal stages of development. This study evaluated the susceptibility to ZIKV infection, viral replication, immune response, and survival of neurons, astrocytes and microglial cells during postnatal developmental stages, using both in vivo and in vitro mice models. In vivo , a non-lethal but extensive infection of neurons and microglia was shown. The infection caused a robust but controlled immune response with elevated levels of MCP-1, TNF-α, and IL-6, that prevented severe neuronal damage. In vitro , neurons exhibited high susceptibility to ZIKV, with elevated levels of pro-inflammatory cytokines and IFN-β, indicating a strong inflammatory response. In contrast, astrocytes and microglia displayed varied responses, contributing to a pro-inflammatory feedback loop. These findings offer critical insights into the cellular dynamics of ZIKV infection, enhancing our understanding of its effects during postnatal nervous system development. By clarifying the interactions between ZIKV and neuronal cell types, this study deepens the comprehension of the virus’s pathophysiology and its broader implications for neurodevelopmental outcomes, extending beyond the well-documented association with microcephaly.